Early Childhood Inclusive Education Improves Creativity And Teacher Competence Early Childhood Education - Hj.Zaharah Binti Awang; Putri Sari Ulfa Sembiring; Kharida Shaleha; Dara Aisyah (Outline Publisher, 2024)
This study aims to determine the importance of inclusive education for early childhood education teachers. The teacher US the play working partners in the process of providing stimulation for child development, in prepare a good and appropriate curriculum in inclusive education is to eliminate differences, discrimination and bullying against children with special needs with this inclusive education will provide good for children, family background also affect towards giving attention and support for children with special needs. Children with unique development are different from one another need inclusive education for early childhood development, inclusive education that is education that carries out learning for all children both normal children and also children with special needs. The aim is for children with special needs to get the same rights in education, in the implementation of inclusive education there are many obstacles including lack of teaching staff, lack of therapist staff, and infrastructure. The development of teacher creativity in educational children is very necessary.